Математическая модель работы электропривода стрелочного перевода на базе линейного двигателя - Буряковский, Сергей Геннадиевич; Маслий, Артем Сергеевич; Любарский, Борис Григорьевич; Маслий, Андрей Сергеевич (Українська державна академія залізничного транспорту, 2015)
В статье рассмотрена математическая модель электропривода на базе линейного электродвигателя с учетом потерь в стали, а также с целью дальнейшего ее использования в качестве основного инструмента при исследовании режимов работы в стрелочном переводе. Это позволит получить динамические характеристики машины. Для моделирования в качестве исходных данных взяты параметры линейного двигателя, предложенного в предыдущих работах. Математическое описание линейного электромеханического преобразователя получено из уравнения Лагранжа.

The article considers mathematical model of electric drive work based on a linear motor. Linear motors are electric induction motors that produce motion in a straight line rather than rotational motion. They are now used in all sorts of machines that require linear (as opposed to rotational) motion, including overhead traveling cranes and beltless conveyors for moving sheet metal. They are probably best known as the source of motive power in the latest generation of high-speed magnetic levitation trains, which promise safe travel at very high speeds but are expensive and incompatible with existing railroads. Many designs have been put forward for linear motors, falling into two major categories, low-acceleration and high-acceleration linear motors. Low-acceleration linear motors are suitable for maglev trains and other ground-based transportation applications. High-acceleration linear motors are normally rather short, and are designed to accelerate an object to a very high speed. The mathematical description of linear electromechanical transducer is derived from the Lagrange equations.
Mathematical model of turnout electric drive work based on a linear motor
Keywords: обобщенные координаты; лагранжиан; линейный электродвигатель; динамические характеристики машины; уравнение Лагранжа; lagrangian; generalized coordinates; Lagrange equations